(untitled) (Agricultural Engineering, 2017)
The paper evaluates operation of the separation unit of NH CR9080 combine harvester. A considerable technical and technological progress has taken place in presently used harvesters. Among others, efficiency increased and equipment has been enhanced with elements which improve the operation quality. The objective of the paper was to determine the quality of the separating unit of a combine harvester New Holland CR9080. During the research, losses on screens and rotor, cutting height of rapeseed, mowing speed, rotation of fans, rotors and engine were determined. Relation of losses on screens to combine operation parameters was determined with a model of multiple regressions. The rotational speed of rotors, mowing speed and rotational speed of the combine engine have a significant effect on losses on screens at the rapeseed harvesting with the investigated combine.